The scientific discourse in singular first person - Duarte Calvo, Antonio (CIC. Cuadernos de Información y Comunicación, 2023)
In this paper I defend the relevance of the subjective gaze in scientific discourse. Firstly, I address this issue through a contemporary and neurobiological approach to creativity. I also rescue Feyerabend’s complaint about the experts’ “ugly” language to articulate the particular connection of these reflections with the activation of one of our neurobiological systems, the brain’s default mode network. This helps me to assess that the scientific discourse in what I call singular first person, not only provides a more accessible narrative to better connect with the audience, but also broadens contextual understanding, providing a more complete view of the knowledge itself. In addition, through a recent example, the discovery of the Higgs boson, I expand this defense by showing how personal remarks (in singular first person) in scientific discourse refer us to a greater context, allowing also a better understanding of the discovery or investigation.